THE INFLUENCE OF SPIRITUAL MOTIVATION, PSYCHOLOGICAL MOTIVATION, PHYSIOLOGICAL MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT HEALTH CENTERS IN THE CITY OF TANJUNGPINANG - Armini; Chablullah Wibisono; Faizal Madya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The existence of HR (Human Resources) in management is truly strategic and is even the key to management success in carrying out various activities to achieve the goals as set. The research method used in this research is mixed methods. Mixed method or combination research is a research method that combines quantitative and qualitative methods. The data analysis technique in this research uses Partial Least Square (PLS). PLS is a Structural Equation Modeling (SEM) model with a variance-based approach or component-based structural equation modeling. From testing the r-square value on employee performance, the Adjusted R-Square for path models using intervening variables is 0.951. This means that the ability of the variables spiritual motivation, psychological motivation, and physiological motivation through job satisfaction in explaining employee performance is 95.1%. Thus, the model is classified as substantial.